Mister Exam
Lang:
EN
EN
ES
RU
Other calculators
Integral Step by Step
Derivative Step by Step
Equation systems Step by Step
Identical expressions
two *(six *x^ two - one) = zero
2 multiply by (6 multiply by x squared minus 1) equally 0
two multiply by (six multiply by x to the power of two minus one) equally zero
2*(6*x2 - 1) = 0
2*6*x2 - 1 = 0
2*(6*x² - 1) = 0
2*(6*x to the power of 2 - 1) = 0
2(6x^2 - 1) = 0
2(6x2 - 1) = 0
26x2 - 1 = 0
26x^2 - 1 = 0
Similar expressions
2*(6*x^2 + 1) = 0
2*(6*x^2 - 1) = 0 equation
+ equation
Solve the equation!
The unknown in the equation:
v
Numerical solution:
Do search numerical solution at [
,
]